1964
DOI: 10.2466/pr0.1964.14.2.491
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Irradiation Saccharin Habituation: A Factor in Avoidance Behavior

Abstract: Seven groups each with eight albino rats were habituated to a 0.1% sodium saccharin solution for either 8, 4, 2, 1, or 0 days prior to x-irradiation or sham-irradiation. The saccharin habituated groups showed a significant decrease in the degree of conditioned saccharin avoidance response as compared with the non-habituated group, but the degree of avoidance response was still significantly different from that of the sham-irradiated group. A group given water to drink prior to irradiation showed no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

1971
1971
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 6 publications
2
3
1
Order By: Relevance
“…The conditioned water aversion found in this study agrees with previous findings (Garcia & Koelling, 1967;Nachman, 1970;Nachman & Jones, 1974). However, others have shown that conditioning with nonnovel solutions resulted in weakened or attenuated taste aversions (Elkins, 1973;Farley, McLaurin, Scarborough, & Rawlings, 1964;McLaurin, Farley, & Scarborough, 1963;Revusky & Bedarf, 1967).…”
Section: Resultssupporting
confidence: 92%
“…The conditioned water aversion found in this study agrees with previous findings (Garcia & Koelling, 1967;Nachman, 1970;Nachman & Jones, 1974). However, others have shown that conditioning with nonnovel solutions resulted in weakened or attenuated taste aversions (Elkins, 1973;Farley, McLaurin, Scarborough, & Rawlings, 1964;McLaurin, Farley, & Scarborough, 1963;Revusky & Bedarf, 1967).…”
Section: Resultssupporting
confidence: 92%
“…In this experiment the data of relative sucrose intake and of sucrose preference reliably showed that pre-exposures to sucrose prior t o toxicosis attenuated taste aversion effects in rats 20 days old. The finding of graded pre-exposure effects in the weanlings is consistent with some data reported for adult rats ( e g , Elkins, 1973;Fenwick ef a/., 1975) but contrasts with other results which showed nondifferential pre-exposure effects with adults (e.g., Farley, McLaurin, Scarborough, & Rawlings, 1964;Kalat & Rozin, 1973). The basis for the discrepancy between the present results and those of Farley etal.…”
Section: Discussionsupporting
confidence: 79%
“…The finding of graded pre-exposure effects in the weanlings is consistent with some data reported for adult rats ( e g , Elkins, 1973;Fenwick ef a/., 1975) but contrasts with other results which showed nondifferential pre-exposure effects with adults (e.g., Farley, McLaurin, Scarborough, & Rawlings, 1964;Kalat & Rozin, 1973). The basis for the discrepancy between the present results and those of Farley etal.…”
Section: Discussioncontrasting
confidence: 56%
“…The purpose of Phase 4 was to insure that, at the time of reconditioning in Phase 5, Group Fam-tox would have had as much recent experience with saccharin as Group Ext-tox. Familiarity of a flavor and the recency of this familiarity are important factors in flavor aversion learning (Farley, McLaurin, Scarborough, & Rawlings, 1964) and hence should be made similar for the two groups. Of course, because Phases 1 and 4 were added to the Fam-tox procedure, corresponding phases were added to the Ext-tox procedure.…”
Section: Methodsmentioning
confidence: 99%